The role of activities supporting the value chain in achieving competitive advantage (A field study in the commercial bank in Latakia Governorate) - سكيف نسرين; سامر قاسم; رامي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to study the role played by activities supporting the value chain in achieving competitive advantage in the Commercial Bank in Latakia Governorate, since the researcher relied on four dimensions of competitive advantage (distinguished cost- distinguished quality- distinguished flexibility- distinguished efficiency). The researcher relied on the descriptive analytical method, since a facilitated sample was used with size of (97). The questionnaire was also used as a tool for collecting primary data and analyzing it through the statistical program (SPSS-26). To test the study hypotheses, the researcher used the Student’s T-test for one sample, as well as simple linear regression analysis. The research reached a set of results, the most important of which are: there was a high level of use of activities supporting the value chain in the commercial bank and its branches in Latakia Governorate, a high level of achieving both distinguished cost and quality as dimensions of competitive advantage, while it was found that there was a low level of achieving both distinguished flexibility and efficiency as dimensions of competitive advantage in the studied bank. The researcher presented a set of recommendations related to the necessity of making effective decisions based on a comprehensive analysis of the basic and supporting activities within the value chain, applying a cost leadership strategy, and achieving excellence in the flexibility component of banking operations.